Escape the Kingdom! Family Business Metaphors in the French Business Press and their Implications for Gendered Representations - Missonier, Audrey (Journal of business ethics, 2025)
Gender biases in the representation of family businesses (FBs) within the business media are subtle, yet pervasive. While previous research emphasised the media’s pivotal role in shaping gender identities, roles, and norms, scant attention has been paid to gendered representations of FBs in the press. Yet FBs are not only the most common form of business organisation, but also a unique workplace context where narratives about women are intertwined with narratives about men, the family, the organisation itself, and the conduct of business; media narratives about FBs thus have far-reaching consequences for society at large. To address this gap, we build on Conceptual Metaphor Theory (CMT) and dissect a selected corpus of 453 articles on FB succession published by the French business newspaper Les Echos, covering an extensive period of 32 years (1991 to 2023). Our results reveal the prevalence and permanence of four metaphors that, while culturally iconic, perpetuate patriarchal views: the family business is (1) a Conquering Kingdom, (2) an Erected Building, (3) a Devouring Giant, or (4) a Racing Machine. Our findings point out that business publications may embrace programmes promoting gender equality while perpetuating a patriarchal system of thought. Bridging gendered representations and business ethics, they underscore the imperative for a critical re-evaluation of gender narratives in business journalism and call for a transformative dialogue that would reshape the narrative landscape, thereby fostering a more inclusive representation of FBs.